WTO's trade policy review mechanism - from through the looking glass. - LAIRD, Sam (1999)
Argues that the mechanism faces a number of challenges in carrying out the mandate set by members, mainly arising from resource constraints. Notes that it is not clear how to carry out the full programme of reviews, especially in the light of the increasing membership of the organisation. Looks at some of the hard choices facing WTO members in this regard.